The Guide to Greening Cities - Johnston, Sadhu Aufochs; Nicholas, Steven S.; Parzen, Julia (Island Press/Center for Resource Economics : Imprint: Island Press, 2013)
Superstorm Sandy sent a strong message that a new generation of urban development and infrastructure is desperately needed, and it must be designed with resilience in mind. As cities continue to face climate change impacts while growing in population, they find themselves at the center of resilience and green city solutions, yet political and budgetary obstacles threaten even the best-planned initiatives. In The Guide to Greening Cities, seasoned green city leaders Sadhu Johnston, Steven Nicholas, and Julia Parzen use success stories from across North America to show how to turn a green city agenda into reality. The Guide to Greening Cities is the first book written from the perspective of municipal leaders with successful, on-the-ground experience working to advance green city goals. Through personal reflections and interviews with leading municipal staff in cities from San Antonio to Minneapolis, the authors share lessons for cities to lead by example in their operations, create programs, implement high-priority initiatives, develop partnerships, measure progress, secure funding, and engage the community. Case studies and chapters highlight strategies for overcoming common challenges such as changes of leadership and fiscal austerity. The book is augmented by a companion website, launching with the publication of the book, which offers video interviews of municipal leaders, additional case studies, and other resources. Rich in tools, insights, and tricks of the trade, The Guide to Greening Cities helps professionals, policymakers, community leaders, and students understand which approaches have worked and why and demonstrates multidisciplinary solutions for creating healthy, just, and green communities.